Using integrated library management systems for the improvement of information services based on cloud computing - Salam Jasim Abdallah; Ghazwan Khalid Ouda (Tikrit Journal of Pure Science, 2020)
With the rapid increase in global intellectual production, academic libraries have been challenged to make this product available to beneficiaries at the perfect time and place. On the other hand, the rapid development in the field of information technology, especially cloud computing and open source software applications, offers many capabilities that can be harnessed in the work of academic libraries to meet the needs of beneficiaries. This paper aims to developing information services in the academic libraries in University of Diyala (UOD) through using cloud computing applications and open source software (Koha) to facilitate the search and retrieval of information by librarians and beneficiaries. A unified research platform has been created for all academic libraries at UOD using Koha integrated system and building a database of bibliographic records, which have been installed on the Google cloud platform. The unified search platform helps librarians and users retrieve information and search resources more efficiently from anywhere, at anytime by calling sources of information with multiple retrieval points (author, source, ISBN, abstract, keywords) as well as the ability to search for sources of information in all UOD libraries simultaneously, which contributes to reducing the time of the beneficiary in obtaining sources of information.